Dinâmica de fósforo e nitrogênio no consórcio de milho com adubos verdes no sistema orgânico - Cardoso, Tainá Martins (Universidade Federal de São Carlos, 2022)
Maize-legume intercropping is an alternative to improve N and P availability in soil/plant system. However, it is necessary to understand nutrients dynamics in soil and its uptake by plants in the intercropping system to optimize the process in organic systems during the same crop year. This work aimed to evaluate effect of intercropping with maize and two species of legume Crotalaria spectabilis Rhot. and Pegeon pea (Cajanus cajan (L.) Millsp.) on soil P and N dynamics, and the relation with the nutrients accumulation in plants and corn grain yield, during the same crop year, in an organic system. The experiment was a factorial design with four levels of intercropping: maize-Crotalaria spectabilis (MC); maize-Pigeon pea (MG); Maize-Crotalaria spectabilis-Pigeon pea (MCG) and maize monocropping (M) and two levels of fertilization: without fertilizer (A) and fertilization using an organic compound (P), with four replications. It measured maize agronomic characteristics like height, dry leaf matter, nutrient accumulation, dry matter of 100 grains, and grain yield. For legumes, it was estimated dry leaf matter and nutrient accumulation. Also, it measured soil NH4- and NO3- concentration, beyond P concentration, pH and the acid and alkaline phosphatases activity in the soil. Maize-Crotalaria spectabilis-Pigeon pea intercropping improved maize N accumulation when compared to Maize intercropping with Pigeon pea. Fertilization using organic manure elevated the NO3- and acid phosphatase activity on soil. Maize-legume intercropping did not affect maize growth neither corn yield. Pigeon pea in an intercropped with maize did not increase P availability to the maize as well did not altered acid and alkaline phosphatases in the soil or soil pH. The maize intercropping with with C. spectabilis and Pegeon pea does not affect plant development, it increases the leaf N content of maize, without effects on grain yield.
Nitrogen and phosphorus dynamics on maize green manure intercropping in organic system
Keywords: Atividade enzimática; Fabaceae; Fixação biológica de nitrogênio; Nutrição mineral; Enzyme activity; Nitrogen biological fixation; Mineral fertilizer; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS BIOLOGICAS::ECOLOGIA